Community-Based Management on Isolated Islands for Socio-economic Development — A systematic review - Rizkina, Fitriana Dina; Takenouchi, Naruhito; Kasamatsu, Hiroki (Agroindustrial Journal, 2025)
This review paper offers a thorough understanding of the literature on research in isolated island communities from the past 10 years. It uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. First, the study identified 190 research papers from reputable international publishers, then selected 23 for the final stage. The review highlights the policy implications of CBM in agriculture (forestry), agroindustry, fisheries, and social science. The review reveals popular research topics discussed in recent studies and provides insight into the methods or approaches used. Our review's results show that specific methods are relevant and are still widely used by 39% of studies. Additionally, future research is expected to explore topics that have not been widely studied, particularly agroindustry. The percentage of agroindustry studies in the CBM review results on isolated islands reflects this situation, representing only 9% of the total, while fisheries represent 52%, social science 22%, and agriculture 17%.